Mauritania : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes economic developments in Mauritania during the 1990s. Significant progress has been achieved in Mauritania since 1992. Economic growth has held up and the rate of inflation has been contained to below 5 percent. The lingering domestic banking crisis was confronted through a comprehensive bank reform. Firm control has been exercised over fiscal and monetary policies, and remedial measures were introduced to cope with unforeseen fiscal outlays for bank restructuring and to counter the impact of a more adverse export environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet